Reimagining future energy systems: Overview of the US program to maximize energy utilization via integrated nuclear‐renewable energy systems. (17th February 2020) - Bragg‐Sitton, Shannon M.; Boardman, Richard; Rabiti, Cristian; O'Brien, James
Summary: A sustainable, balanced energy portfolio is necessary for a country's continued economic growth. This portfolio must collectively be able to provide reliable, resilient electricity at stable, affordable prices. Nuclear energy is an important contributor to global clean energy supply, both as a primary source and by complementing and enabling other clean energy sources. As we look to the design and operation of future energy systems, we see an increasing need to think differently about how we utilize our energy resources to meet all of our energy needs—not just electricity but also industrial and transportation demands. Resource utilization in light of a broader desire to reduce environmental impacts leads us to consider transforming how we use nuclear energy, which currently provides more than half of the nonemitting electricity generated in the United States. A paradigm shift is required to develop optimal energy generation and use configurations that embrace novel approaches to system integration and process design. The US Department of Energy (DOE) Office of Nuclear Energy (NE) program on Integrated Energy Systems (IES)—formerly the Nuclear‐Renewable Hybrid Energy Systems (N‐R HES) program—was established to evaluate potential options for the coordinated use of nuclear and renewable energy generators to meet energy demands across the electricity, industrial, and transportation sectors. These formerly independent sectors are becoming increasingly linked through technology advances in data acquisition, communications, demand response approaches, and control technologies. Advanced modeling and simulation tools can be employed to design systems that better coordinate across these sectors. Implementation of integrated multi‐input, multi‐output energy systems will allow for expanded use of nuclear energy beyond the grid in a manner that complements the increased build‐out of variable renewable energy generation. These integrated systems would provide enhanced flexibility while also providing energy services and supporting the production of additional, nonelectric commodities (eg, potable water, hydrogen, and liquid fuels) via excess thermal and electrical energy from the nuclear system. Increased flexibility of traditionally baseload nuclear systems will support energy security, grid reliability, and grid resilience while maximizing the use of clean energy technologies. This paper provides an overview of current efforts in the United States that assess the potential to increase utilization of nuclear energy systems, in concert with renewable energy generation, via the IES program. Analysis tools and approaches and preliminary analysis results are summarized, and planned experimental activities to demonstrate integrated system performance are introduced. Abstract : Nuclear energy is an important contributor to global clean energy supply, both as a primary source and by complementing and enabling other clean energy sources. Increased flexibility of traditionally baseload nuclear systems will support energy security, grid reliability, and grid resilience while maximizing the use of clean energy technologies. This paper provides an overview of current efforts in the United States to increase utilization of nuclear energy systems, in concert with renewable energy generation, via the DOE Integrated Energy Systems program.